Contribution to the taxonomy of Turkish Scorzonera (Asteraceae) taxa based on vegetative anatomy. (26th May 2016) - Makbul, Serdar; Coşkunçelebi, Kamil; Okur, Seda; Gültepe, Mutlu
Abstract : In the present study, the general stem, root and leaf anatomical features of 59 Scorzonera L. s.l. (Asteraceae) taxa collected from Turkey are presented and evaluated by cluster and principal coordinate analysis. Numerical analyses based on 26 anatomical traits showed that arrangement of tracheal elements in the root, presence of cortical bundles, latex canals, secretory cells and aerenchyma in the stem and mesophyll are valuable for grouping Scorzonera taxa. Dendograms inferred from anatomical data were generally congruent with the traditional subgeneric classification of Scorzonera ( Scorzonera L., Podospermum DC., Pseudopodospermum (Lipsch. et Krasch.) Lipsch.). However, the present study also show that the examined species may not be identified only based on the internal morphology of root, stem and leaf. In addition, the results support to treat Podospermum as a distinct genus.